PERAN PROFESIONALISME AUDITOR DALAM MENGUKUR TINGKAT MATERIALITAS PADA PEMERIKSAAN LAPORAN KEUANGAN - YOHANNES CHRISTIAN (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
The information presented in the financial statements will be used as a basis for decision making. Examination of financial statements performed by the auditor and received unqualified opinion, is expected to provide assurance that the financial statements are free of material misstatement and are presented with accounting principles generally acceptable. Professionalism major demand of someone working as an auditor. Picture of someone who is professional in the profession of auditor reflected in five dimensions: dedication to the profession, social obligations, independence, confidence in the rules of the profession, and relationships with colleagues. In conducting the audit of financial statements, auditors are required to make consideration of the level of materiality in planning and designing audit procedures, as well as evaluating the fairness of the financial statements as a whole.